2012
DOI: 10.1176/appi.ajp.2012.11091365
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants May Mitigate the Effects of Prenatal Maternal Anxiety on Infant Auditory Sensory Gating

Abstract: Objective Prenatal maternal anxiety has detrimental effects on the resulting offspring’s neurocognitive development, including impaired attentional function. Antidepressants are commonly utilized during pregnancy, yet their impact on offspring attention and their interaction with maternal anxiety has not been assessed. Using P50 auditory sensory gating, a putative marker of early attentional processes measurable in young infants, the impact of maternal anxiety and antidepressant use are explored. Method Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 70 publications
(58 reference statements)
1
25
0
Order By: Relevance
“…=49, p<.001) than response to the first stimulus (2.29±1.12 μV) demonstrating the presence of sensory gating. Mean ± standard deviation for P50 sensory gating ratios was 0.44±0.31, consistent with reported infant values (Hunter et al, 2011; Hunter et al, 2012). Those infants with robust sensory gating were older than infants with diminished sensory gating although the difference did not reach significance and no relationship between age and P50 sensory gating values has previously been identified (Suzuki & Azuma, 1977).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…=49, p<.001) than response to the first stimulus (2.29±1.12 μV) demonstrating the presence of sensory gating. Mean ± standard deviation for P50 sensory gating ratios was 0.44±0.31, consistent with reported infant values (Hunter et al, 2011; Hunter et al, 2012). Those infants with robust sensory gating were older than infants with diminished sensory gating although the difference did not reach significance and no relationship between age and P50 sensory gating values has previously been identified (Suzuki & Azuma, 1977).…”
Section: Resultssupporting
confidence: 88%
“…Having a parent with psychosis as a presumed increased genetic vulnerability or a mother with anxiety, and/or prenatal exposure to nicotine or other illicit substances as possible environmental risk factors are well-established larger effect size risk factors for later attention-driven behavioral impairment. Each of these risk factors is associated with impaired infant P50 sensory gating, with effects identifiable in even relatively small samples (Hunter, Kisley, McCarthy, Freedman, & Ross, 2011; Hunter et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Prescribing a drug for a pregnant woman results from the physician’s judgment that her health is best served by treatment of the disorder, yet our literature is largely focused upon negative outcomes rather potential positive impacts on maternal disease and child outcomes (33, 34). For example, Hunter et al (35), demonstrated that infants born to mothers with anxiety disorders had impaired P50 auditory gating (a marker of infant attentional processing). Their novel finding was that maternal antidepressant treatment during pregnancy improved sensory gating in the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal nicotinic acetylcholine receptors (nAChRs) modulate anxiety- and depressive-related behaviors in adult animals [79], and are also sensitive to corticosterone and psychological stress in adulthood [1012]. Furthermore, cholinergic abnormalities are associated with anxiety and depression in humans [1318]. In rodents, prenatal stress alters levels of both alpha7* and alpha4 beta2* hippocampal nAChRs [19], and alters stress-dependent hippocampal cholinergic function in adulthood [20], suggesting that the effects of prenatal stress on anxiety-related behaviors may be driven by altered development of the hippocampal cholinergic system.…”
Section: Introductionmentioning
confidence: 99%